Effect of threonine level in a high-protein diet on the growth performance and carcass characteristics of 50- to 91-day-old slow-growing indigenous male Boschveld chickens - Sekgotodi, Tebogo Mack; Ng’ambi, Jones Wilfred; Manyelo, Tlou Grace (Frontiers in Animal Science, 2025)
Broiler chickens are economically, nutritionally, and culturally very important. An experiment was conducted to determine the effect of dietary threonine level on the growth performance of slow-growing 50- to 91-day-old male Boschveld chickens. A total of 75 chickens were used in a complete randomized design comprising five dietary treatments, with three replicates and five chickens per replicate. The dietary treatments had similar nutrient contents but different threonine levels: 4.0, 7.5, 8.0, 8.5, and 9.0 g/kg dry matter (DM). The collected data were subjected to one-way analysis of variance using SAS version 9.4. A quadratic equation was used to determine the dietary threonine levels for the optimal performance of the chickens. The threonine levels affected (p<0.05) the feed intake, body weight gain, feed conversion ratio, metabolizable energy intake, nitrogen retention, abdominal fat weight, and the meat crude protein and threonine levels of the chickens. The body weight gain, feed conversion ratio, metabolizable energy intake, nitrogen retention, abdominal fat weight, and the meat crude protein and threonine levels of the chickens were optimized at dietary threonine levels of 6.12, 6.82, 5.71, 6.0, 6.9, 5.9, and 5.7 g/kg DM, respectively. However, the feed intake of the chickens decreased (p<0.05) when the dietary threonine levels were increased. The dietary threonine levels did not affect (p<0.05) the pH values of chicken meat. However, the threonine level in the diet affected (p<0.05) the chicken meat color. The chicken meat lightness and the hue angle had a positive relationship (p<0.05) with the dietary threonine levels, while the meat redness, yellowness, and chroma had a negative relationship (p<0.05) with the dietary threonine levels. It was concluded that the production parameters of male Boschveld chickens were optimized at different dietary threonine levels.